2011
DOI: 10.1111/j.1478-4408.2011.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave pretreatment on the dyeing behaviour of polyester fabric

Abstract: Polyester fabric (filament by filament) was pretreated in a microwave oven in the presence of solvents and subsequently dyed with commercial disperse dyes [Dispersol Red C-B (CI Disperse Red 91) and Dispersol Blue B-G (CI Disperse Blue 26)] at different temperatures and for different durations of time. It was observed that the solvent interaction with the polyester could be enhanced by using microwave heating. Solvent molecules interact rapidly, not only with the surface of the fibre but also with the interior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 15 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…This leads to advantages such as rapid, controlled, selective and uniform heating. Moreover, it is known that microwave heating enhances diffusion of organic molecules in polymers and this can increase the fixing rate of dyes into the polymeric textiles .…”
Section: Discussionmentioning
confidence: 99%
“…This leads to advantages such as rapid, controlled, selective and uniform heating. Moreover, it is known that microwave heating enhances diffusion of organic molecules in polymers and this can increase the fixing rate of dyes into the polymeric textiles .…”
Section: Discussionmentioning
confidence: 99%
“…Polyester dyeing: J. Kale Manik et al [43] studied the solvent (DMF) pretreated of polyester fabric by using microwave oven to enhance its dyeability with commercial disperse dyestuff; the dyeing process was carried out by exposure the polyester fabric to microwave irradiation at different temperature and different interval time. The results revealed that the microwave irradiation enhanced the interaction of solvent with the polyester fabrics, solvent molecules react quickly, not only with the fibers K. Haggag et al [47] surface but also with the internal parts.…”
Section: Dyeing Of Wool Fabricmentioning
confidence: 99%
“…Microwave modification technology is a new research direction for low energy consumption and low equipment requirement for textile processing (Haggag, El-Sayed, & Allam, 2007;Kale & Bhat, 2011;Kalia & Sheoran, 2011;Ramadan, EI Sayed, & Almetwally, 2012;Sun, Lin, & Bai, 2005). In recent years, modifications and dyeing of some materials have been conducted using microwave irradiation; however, the reports on the effect of microwave irradiation on the dyeability properties of wool are scanty.…”
Section: Introductionmentioning
confidence: 97%